2009
DOI: 10.1029/2008gc002312
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary, volcanic, and tectonic processes of the central Mariana Arc: Mariana Trough back‐arc basin formation and the West Mariana Ridge

Abstract: [1] We present new multichannel seismic profiles and bathymetric data from the central Marianas that image the West Mariana Ridge (WMR) remnant arc, both margins of the Mariana Trough back-arc basin, the modern arc, and Eocene frontal-arc high. These data reveal structure and stratigraphy related to three periods of arc volcanism and two periods of arc rifting. We interpret the boundary between accreted backarc basin and rifted arc crust along the Mariana Trough and support these findings with drilling results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 97 publications
(162 reference statements)
3
26
0
Order By: Relevance
“…Rose diagrams show that fault orientations are perpendicular to the backarc spreading direction (Figure ). This is consistent with the interpretation of Oakley et al () that the faults are associated with spreading. The arc‐segment azimuths are subparallel to the fault orientations.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Rose diagrams show that fault orientations are perpendicular to the backarc spreading direction (Figure ). This is consistent with the interpretation of Oakley et al () that the faults are associated with spreading. The arc‐segment azimuths are subparallel to the fault orientations.…”
Section: Resultssupporting
confidence: 93%
“…The backarc spreading rates are 15.9 ± 6.6 mm/year with an azimuth of 57.8° ± 19.9° near Agrigan at the center of the arc, with a maximum rate of 44.6 ± 2.7 mm/year directed toward 97.1° ± 4.1° near Guam in the south (Kato et al, ). This study also showed lateral, N‐S motion in the residual data, which aligned with the model of spreading developing in the center of the trough propagating to the north and south (Martínez et al, ; Oakley et al, ).…”
Section: Mariana Arcsupporting
confidence: 84%
“…10 Ma) of the arc compared to the more complex, longer-lived Tonga-Kermadec, Mariana and Izu-Bonin intra-oceanic arcs (Ishizuka et al, 2003; I.J. Oakley et al, 2009;Wysoczanski et al, 2010). Most of the volcanic front volcanoes have summits 3.0-3.5 km above base levels, which are deeper in the north (2500-3000 m) than in the south (2000-2500 m).…”
Section: Volcanic Development and Structure Of The Arcmentioning
confidence: 99%
“…In the southwest Pacific, the three types are geographically separated in Solomon Islands and Vanuatu (Greene and Wong 1988;Petterson et al 1999). More common are en echelon lines of limestone (forearc) and volcanic islands running parallel to an adjacent trench axis, such as are found in Tonga and the Marianas islands (Nunn 1998b;Oakley et al 2009). In their simplest expression, usually where subduction began only comparatively recently, a single line of young volcanic islands is found; examples are found in the Aleutian and Kurile groups in the northernmost Pacific as well as parts of Papua New Guinea (Prueher and Rea 2001;Silver et al 2009).…”
Section: Island Locationsmentioning
confidence: 99%